Advanced phase analysis of retinal videos using ECG - Šíma, Jan; Němcová, Andrea; Kolář, Radim (Lékař a technika, 2024)
Spectral analysis is one way to further investigate retinal hemodynamics and vessel pulsation. Specifically, for the phase component of the spectrum of retinal videos, the significance in retinal analysis has not yet been fully defined. The aim of this study is to determine whether the value of phase is relevant in the classification of blood vessels (arteries and veins). Using electrocardiographic signals recorded simultaneously with retinal video, we can determine how the phase component of the video behaves with respect to the cardiac cycle. As part of the experiment, we measured the retinal video of the left eye of 13 healthy subjects. We found that the phase delay between the maximal pulsation of arteries and veins in the optic nerve head tissue is on average 9% of the actual cardiac period. For our data set, this corresponds to an average time delay of 80.22 ms. We conclude that this phase delay between pulsations of arteries and veins can help in the classification of vessels in the optic nerve head.